Precontrast T1 signal measurements of normal pituitary and microadenoma: A retrospective analysis through DCE MRI signal time curves - Kumar, Ishan; Yadav, Tanya; Verma, Ashish; Shukla, Ram C; Singh, Surya K (Indian Journal of Radiology and Imaging, 2018)
Background: The dynamic contrast enhanced magnetic resonance imaging (DCE MRI) has currently become the most utilized technique for the detection of pituitary microadenoma. However, owing to differential enhancement of normal pituitary, high rate of false positivity remains a concern in its interpretation. Purpose: Our aim was to assess the utility of precontrast T1 signal intensity ratio (SIR) of the lesions suspected on DCE MRI, in prediction of presence of microadenoma. Materials and Methods: We retrospectively reviewed MRI of 23 patients referred for DCE MRI of pituitary (group 1, 15 patients with diagnosis of pituitary microadenoma; and group 2, patients not clinically labeled as microadenoma). STC were plotted and T1-SIR at t = 0 s was obtained at the suspicious zone of differential enhancement (SIR T) and normal pituitary (SIR P). SIR difference (SIR P − SIR T) and relative SIR difference (SIR P − SIR T/SIR P) were calculated for each patient and was compared between the two groups. Results: Mean T1 SIR is lower in patients with microadenoma than those without (P = 0.065). SIR difference and relative SIR difference was higher in patients with microadenoma (P = 0.003 and 0.005, respectively). Receiver-operated characteristic curve analysis demonstrated that a cut-off of 26 and 0.107 for SIR difference and relative SIR difference, respectively, could diagnose microadenoma with 100% specificity and reasonable sensitivities. Conclusion: The baseline precontrast T1 SIR evaluation of the lesion suspected to be microadenoma on DCE MRI, derived through STC curve, can increase diagnostic confidence in diagnosis of microadenoma.
Keywords: Dynamic contrast magnetic resonance imaging; pituitary microadenoma; signal time curve